Endovascular Exclusion of Mycotic Aortic Aneurysm - Takach, Thomas J. (Texas Heart Institute, 2007)
The presence of prohibitive risk may preclude usual surgical management. Such was the case for a critically ill, 60-year-old woman who presented with concomitant, life-threatening conditions. The patient presented with acute central cord syndrome and lower-extremity paraplegia after completing a 6-week course of intravenous antibiotics for methicillin-sensitive Staphylococcus aureus bacteremia and osteomyelitis of the thoracic spine. Radiologic examination revealed bony destruction of thoracic vertebrae T4 through T6, impingement on the spinal cord and canal by an inflammatory mass, and a separate 2.5-cm mycotic aneurysm of the infrarenal aorta. The clinical and radiologic findings warranted immediate decompression and stabilization of the spinal cord, aneurysmectomy, and vascular reconstruction. However, the severely debilitated patient could not tolerate 2 simultaneous open procedures. She underwent emergent endovascular exclusion of the mycotic aneurysm with a stent-graft, followed immediately by laminectomy and stabilization of the thoracic spine. Intraoperative microbiology specimens showed no growth. The patient was maintained on prophylactic antibiotic therapy for 6 months. Fourteen months postoperatively, her neurologic function was near full recovery, and neither surveillance blood cultures nor radiologic examinations showed a recurrence of infection or aneurysm. Although the long-term outcome of endovascular stent-grafts in the treatment of culture-negative mycotic aneurysms is unknown, the use of these grafts in severely debilitated patients can reduce operative risk and enable recovery in the short term.